Polypharmacy and Potential Drug Interactions Causing Neurological Symptoms in Geriatric Patients with Epilepsy - Bahar Erbaş (Archives of Epilepsy, 2022)

(untitled)
Objective:Polypharmacy brings with it the risk of potential drug interaction. This study aimed to investigate polypharmacy, potential drug interactions, the drug interactions causing neurological symptoms in geriatric patients with epilepsy, and diffenrences between drug interaction databases.Methods:The study included patients with epilepsy aged 65 and over (the demographic information, antiepileptic drug use, other chronic diseases, and medications of the patients were retrospectively recorded from their files). The use of 5 or more drugs was accepted as polypharmacy. Potential drug interactions were checked from 2 open access databases (database-1; database-2), and interacting drugs, interaction types, clinical results, and differences between databases were determined.Results:This study included 126 patients (56 females/70 males), the mean age was 73.13 ± 7.42 (65-92), and the mean duration of antiepileptic drug (69.8% monotherapy) use was 9.08 ± 13.68 (0.5-58) years. The most commonly used antiepileptic drug was levetiracetam (69.8%). Totally 88 patients had at least 1 central nervous system disease (except epilepsy), and 116 had a chronic diseases other than central nervous system disease. Polypharmacy frequency was 75.4%. The most commonly used drug groups with the highest potential drug interaction risk were antihypertensives (69%), antia ggreg ant-a ntico agula nts (67%), statins (44%), proton pump inhibitors (41%), and antidepressants (39%). The major, intermediate, and minor potential drug interactions for database-1 and database-2 were 44 versus 53; 586 versus 428, and 127 versus 70, respectively. The most important potential drug interactions were the increased risk of hemorrhage and thrombotic events, arrhythmia, and blood pressure changes.Conclusion:It is important to know about potential drug interactions (especially involving cardiac drugs, antidepressants, statins, and proton pump inhibitors) in the evaluation of the entire neurological picture of geriatric epilepsy patients.